Understanding Energy Innovation Learning from Smart Grid Experiments - Lovell, Heather (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
'Setting out to de-mystify energy innovation, this book provides a comprehensive, grounded and accessible overview of the insights that a social perspective on energy transitions brings. With a focus on smart grids, drawing on examples from Australia and around the world, it explores the dynamics of innovation in practice, the stories we tell about it, and how nostalgia for times gone past will shape energy futures. A practical, insightful guide for the transition pathways ahead.' -Professor Harriet Bulkeley, Durham University, and Copernicus Institute of Sustainable Development, Utrecht University 'The electricity grid already was a uniquely complex machine so what does it take to make it "smart"? Engineering can detail the material ingredients, but only the social sciences can explain the messy process of trying to make such innovations happen. In the short space of this unique book, Lovell provides expert guidance to the social science theories behind innovation, sheds new light on Australia's smart grid experiments and (wait for it) explains why nostalgia matters.' -Dan van der Horst, Professor of Energy, Environment and Society, University of Edinburgh 'Lovell presents an accessible and insightful framework for considering energy innovation. Through current case studies, she makes a powerful argument for more attention to be given to the social and human dimensions of innovation in the energy transition. This is a valuable contribution for those who commission and fund energy research, those who undertake research, and those who use the results.' -Drew Clarke, Chair, Australian Council of Learned Academies (ACOLA) 'Australian Energy Transition Research Plan' This open access book uses smart grids to explore and better understand energy innovation, from a social science perspective. It provides ways to think about and plan for energy sector reform and innovation, drawing on core ideas from social and innovation theory, and centred on smart grids as a case study. Heather Lovell is Professor of Energy and Society at the University of Tasmania, Australia.